Seasonal scenario planning for matching seed supply and demand: Final report - Steinke, Jonathan; Ortíz Crespo, Berta (2022)
Probabilistic scenario planning in agriculture is a procedure that uses available data and expert estimates to inform decision-making across the food system in a way that minimizes economic risk. This report summarizes the sustained application of the project outputs. It includes a synthesis of a project reflection event and of the overall project, highlighting the main findings.